Anansi and the talking melon - Kimmel, Eric A.; Stevens, Janet (New York : Holiday House, 1994)
Anansi, a clever spider, tricks Elephant and some other animals into thinking the melon in which he is hiding can talk.
*SLJ*
Booklist
Kirkus Reviews
3.9
K-3
Keywords: Anansi (Legendary character) -- Legends; Anansi (Legendary character); Folklore -- Africa; Anansi (Legendary character); Folklore -- Africa